Paste composition for preparing solar cell electrode, solar cell electrode and solar cell

By using a specific ratio of glass powder in the paste composition of the solar cell electrode, the problem of opening pressure reduction caused by aluminum spikes is solved, and higher battery efficiency and long-term reliability are achieved.

CN118471579BActive Publication Date: 2025-02-18DK ELECTRONICS MATERIALS INC
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410619955.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-17
Publication Date
2025-02-18
Estimated Expiration
2044-05-17

AI Technical Summary

Technical Problem

In the prior art, the formation of aluminum spikes between the solar cell electrode prepared from typical components such as lead-containing glass powder and the silicon substrate emitter is significantly reduced, which affects the battery efficiency.

Method used

A paste composition for preparing a solar cell electrode is provided, including a conductive powder, an organic carrier, a glass powder and a residual additive. The glass powder contains 10 wt% to 90 wt% PbO, 5 wt% to 90 wt% B2O3, and 1 wt% to 40 wt% of forming oxides, selected from the group VA element oxide, IVB element oxide and VB One or more of the group consisting of group element oxides.

Benefits of technology

The electrodes produced by the paste composition can minimize over-etching of the passivation layer by ordinary glass powder, reduce contact resistance and improve acid resistance, thereby improving the efficiency and long-term reliability of solar cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0005159651190000081
    Figure GDA0005159651190000081
  • Figure GDA0005159651190000091
    Figure GDA0005159651190000091
Patent Text Reader

Abstract

The present invention provides a paste composition for preparing a solar cell electrode, a solar cell electrode and a solar cell. The paste composition for preparing a solar cell electrode comprises a conductive powder, an organic carrier, a glass powder, and a balance of additives, wherein the glass powder comprises: 10wt% to 90wt% of PbO; 5wt% to 90wt% of B2O3; and 1wt% to 40wt% of a forming oxide, wherein the forming oxide is selected from one or more of the group consisting of oxides of group VA elements, oxides of group IVB elements and oxides of group VB elements, and the sum of all components in the glass powder is 100wt%. Through the paste composition for preparing a solar cell electrode of the present invention, in the production process, the over-etching of a passivation layer by ordinary glass powder can be minimized, and at the same time, the electrode made by the glass powder of the present invention reduces the contact resistance and improves the acid resistance, thereby improving the efficiency and long-term reliability of the solar cell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of solar cells, and in particular to a paste composition for preparing solar cell electrodes, a solar cell electrode and a solar cell. Background Art

[0002] A solar cell is a device that can convert sunlight directly into electrical energy, also known as a photovoltaic cell. It consists of many photovoltaic cells that use the energy of photons to release electrons, thereby generating an electric current. Solar cells are widely used in solar power systems, which can provide clean, renewable energy for homes and industrial facilities. They are usually made of semiconductor materials such as silicon, which have the advantages of long life and low maintenance costs. As the demand for renewable energy grows, solar cells are becoming more and more widely used in the energy field.

[0003] Solar cells use the photovoltaic effect to convert photons of sunlight through pn junctions to generate electrical energy. In solar cells, a front electrode and a back electrode are formed on the upper and lower surfaces of a semiconductor chip or substrate having a pn junction, respectively. Sunlight entering the semiconductor chip causes the photoelectric effect of the pn junction, and the electrons generated by the photoelectric effect of the pn junction further provide current to the outside world through the solar cell electrodes. In the process of preparing solar cells, a composition (paste) for electrodes is usually placed on a chip, patterned and baked to form the electrodes of the solar cell.

[0004] Currently, n-type TOPCon solar cell technology has become the mainstream technology in the solar industry due to its high energy efficiency. This technology utilizes a boron-diffused p+ emitter and a tunneling oxide passivation contact layer (TOPCon) on the back, combined with a phosphorus-doped polysilicon layer (n-type Cz-Si), to achieve excellent photoelectric conversion performance. Traditional silver-aluminum paste may form aluminum spikes during electrode preparation, which can cause Joe-met metal composite losses on the metal electrode on the electrode side, affecting cell efficiency. Therefore, TOPCon cell manufacturers use laser enhanced contact optimization (LECO) technology, which can precisely locally destroy the passivation layer through lasers to improve electron transfer between metal and silicon. Cells using n-type TOPCon solar cell technology use silver paste instead of silver-aluminum paste, which reduces the formation of aluminum spikes and effectively improves the open circuit voltage and overall efficiency of the cell.

[0005] However, although n-type TOPCon solar cell technology and n-type TOPCon solar cell technology can improve the performance of individual cells, in practical applications, multiple solar cells still need to be connected to each other through welding ribbons to form solar cell modules. This connection process is crucial because it directly affects the performance and durability of the entire solar cell module. In the manufacturing process of solar cell modules, battery electrodes usually use traditional materials such as lead glass powder to improve the bonding strength between the welding ribbon and the battery electrode. However, these traditional materials are still insufficient in bonding strength, especially when the adhesion between the electrode and the welding ribbon is low, which will lead to an increase in series resistance, thereby reducing the photoelectric conversion efficiency. Summary of the invention

[0006] The main purpose of the present invention is to provide a paste composition for preparing solar cell electrodes, solar cell electrodes and solar cells, so as to solve the problem in the prior art that the solar cell electrodes prepared from typical components such as lead-containing glass powder and the silicon substrate emitter are formed with aluminum spikes, thereby significantly reducing the opening voltage of the cell and affecting the cell efficiency.

[0007] To achieve the above-mentioned purpose, according to one aspect of the present invention, there is provided a paste composition for preparing solar cell electrodes, which comprises a conductive powder, an organic carrier, a glass powder, and the remainder of additives, wherein the glass powder comprises: 10wt% to 90wt% of PbO; 5wt% to 90wt% of B2O3; and 1wt% to 40wt% of a forming oxide, wherein the forming oxide is selected from one or more of the group consisting of oxides of group VA elements, oxides of group IVB elements and oxides of group VB elements.

[0008] In the above paste composition, the shaped oxide is selected from one or more of the group consisting of P2O5, As2O3, TiO2, Sb2O3, Sb2O5, Bi2O3, Bi2O5, V2O5, NbO2, Ta2O5, ZrO2 and HfO2; preferably, the shaped oxide is selected from one or more of the group consisting of TiO2, P2O5 and V2O5.

[0009] In the above paste composition, the glass powder further contains 1wt% to 50wt% of other oxides, and the other oxides are selected from one or more of the group consisting of Li2O, Na2O, K2O, MgO, CaO, SrO, BaO, SiO2 and ZnO; preferably, the other oxides are selected from one or more of the group consisting of SiO2, ZnO and Li2O.

[0010] In the above paste composition, the glass powder includes: 10wt% to 90wt% of PbO; 5wt% to 90wt% of B2O3; 1wt% to 30wt% of P2O5 or V2O5; and 1wt% to 20wt% of TiO2, and the total of all components in the glass powder is 100wt%.

[0011] The paste composition comprises 60wt% to 95wt% of conductive powder, 1.0wt% to 20wt% of organic vehicle, 0.1wt% to 5wt% of glass powder, and the remainder of additives, and the total of all components in the paste composition is 100wt%.

[0012] In the above paste composition, the additive is one or more selected from the group consisting of a dispersant, a thixotropic agent, a plasticizer, a viscosity stabilizer, a defoaming agent, a pigment, a UV stabilizer, an antioxidant and a coupling agent.

[0013] In the above paste composition, the conductive powder is one or more selected from the group consisting of silver powder, copper powder, aluminum powder, nickel powder, carbon black powder, gold powder, platinum powder and titanium powder.

[0014] In the above paste composition, the organic vehicle is one or more selected from the group consisting of an organic solvent, a binder, a plasticizer and a surfactant.

[0015] According to another aspect of the present invention, there is provided a paste composition for preparing solar cell electrodes, comprising a conductive powder, an organic carrier, a glass powder, and the remainder of additives, wherein the glass powder comprises: 10 wt % to 90 wt % of PbO; 5 wt % to 90 wt % of B2O3; 1 wt % to 40 wt % of ZnO; and 1 wt % to 40 wt % of a forming oxide, wherein the forming oxide is selected from one or more of the group consisting of oxides of group VA elements, oxides of group IVB elements, and oxides of group VB elements, and the sum of all components in the glass powder is 100 wt %.

[0016] According to another aspect of the present invention, there is provided a paste composition for preparing solar cell electrodes, comprising a conductive powder, an organic carrier, a glass powder, and the remainder of additives, wherein the glass powder comprises: 10 wt % to 90 wt % of PbO; 5 wt % to 90 wt % of B2O3; 1 wt % to 40 wt % of ZnO; 1 wt % to 30 wt % of SiO2; and 1 wt % to 40 wt % of a forming oxide, wherein the forming oxide is selected from one or more of the group consisting of oxides of group VA elements, oxides of group IVB elements, and oxides of group VB elements, and the sum of all components in the glass powder is 100 wt %.

[0017] According to another aspect of the present invention, there is provided a paste composition for preparing solar cell electrodes, comprising a conductive powder, an organic carrier, a glass powder, and the remainder of additives, wherein the glass powder comprises: 10 wt % to 90 wt % of PbO; 5 wt % to 90 wt % of B2O3; 1 wt % to 40 wt % of ZnO; 1 wt % to 30 wt % of SiO2; and 1 wt % to 20 wt % of TiO2, and the sum of all components in the glass powder is 100 wt %.

[0018] According to another aspect of the present invention, a solar cell electrode is provided, which is prepared from the paste composition described above in the present invention.

[0019] According to another aspect of the present invention, a solar cell is provided, which includes an electrode, which is the solar cell electrode described above according to the present invention; preferably, the solar cell is a solar cell produced using laser enhanced contact optimization technology or a solar cell produced using back contact cell technology.

[0020] By using the paste composition for preparing solar cell electrodes, solar cell electrodes and solar cells of the present invention, excessive etching of the passivation layer by ordinary glass powder can be minimized during the production process of LECO solar cells. At the same time, the electrodes made from the glass powder of the present invention reduce contact resistance and improve acid resistance, thereby improving the efficiency and long-term reliability of the solar cell. DETAILED DESCRIPTION

[0021] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.

[0022] Currently, in the solar cell manufacturing industry, laser enhanced contact optimization (LECO) technology is widely used to improve the photoelectric conversion efficiency of n-type TOPCon cells. LECO technology is an advanced laser sintering method that processes the front surface of the cell through precisely controlled laser scanning. This process produces a high concentration of carrier injection on the surface. During the process, a reverse bias is applied to the cell at the same time, which helps to enhance the contact effect between metal and silicon.

[0023] Under the influence of LECO technology, the metal / semiconductor contact interface of silver / silicon will produce high current concentration under the combined effect of high carrier injection and reverse bias. This high current concentration helps to form a lower contact resistance at the contact point, thereby optimizing the electronic interface of metal / silicon, greatly improving the electronic transmission performance of the electrode and the output efficiency of the entire battery.

[0024] However, as described in the background technology, in the prior art, the solar cell electrode prepared by typical components such as lead-containing glass powder and the silicon substrate emitter has a significant reduction in the opening voltage of the battery due to the formation of aluminum spikes, which affects the further improvement of the battery efficiency. In view of the problems existing in the prior art, according to a typical embodiment of the present application, a paste composition for preparing solar cell electrodes is provided. The paste composition comprises a conductive powder, an organic carrier, a glass powder, and the remainder of additives. In the glass powder, 10wt% to 90wt% of PbO, 5wt% to 90wt% of B2O3, and 1wt% to 40wt% of a forming oxide are contained, and the forming oxide is selected from one or more of the group consisting of oxides of group VA elements, oxides of group IVB elements, and oxides of group VB elements.

[0025] By applying the paste composition for preparing solar cell electrodes of the present invention, excessive etching of the passivation layer by ordinary glass powder can be minimized during the production process of LECO solar cells. At the same time, the electrodes made from the glass powder of the present invention have reduced contact resistance and improved acid resistance, thereby improving the efficiency and long-term reliability of the solar cells.

[0026] In the technical solution of the present invention, the glass powder contains 10wt% to 90wt% of PbO. PbO within this range can increase the refractive index of the battery electrode, making it easier for light to be absorbed by the solar cell; improve the heat resistance of the battery electrode, so that it can maintain stability at high temperatures; and can help connect the battery electrode with the welding strip, improving the performance and stability of the battery. The glass powder of the present invention also contains 5wt% to 90wt% of B2O3. Within the above numerical range, B2O3 can reduce the melting point of the battery electrode, making the glass powder easier to melt into glass, which is beneficial to the preparation process; and B2O3 can increase the acid and alkali corrosion resistance of the battery electrode, so that the battery electrode can better resist the erosion of the external environment and extend the service life of the battery; in addition, B2O3 can adjust the thermal expansion coefficient of the battery electrode, so that the battery electrode is better matched with other materials, reducing cracks and damage caused by mismatched thermal expansion coefficients.

[0027] In different embodiments of the present invention, the content of PbO may be in the following range: 10wt% to 90wt%, 20wt% to 80wt%, 30wt% to 70wt%, 40wt% to 60wt%, 10wt% to 80wt%, 10wt% to 70wt%, 10wt% to 60wt%, 10wt% to 50wt%, 10wt% to 40wt%, 10wt% to 30wt%, 10wt% to 20wt%, 20wt% to 90wt%, 30wt% to 90wt%, 40wt% to 90wt%, 50wt% to 90wt%, 60wt% to 90wt%, 70wt% to 90wt% or 80wt% to 90wt%. For different embodiments, the content of B2O3 can be in the following range: 5wt% to 89wt%, 10wt% to 85wt%, 15wt% to 80wt%, 20wt% to 75wt%, 25wt% to 70wt%, 30wt% to 65wt%, 35wt% to 60wt%, 40wt% to 55wt%, 45wt% to 50wt%, 5wt% to 80wt%, 5wt% to 70wt%, 5wt% to 60wt%, 5wt% to 50wt%, 5wt% to 40wt%, 5wt% to 30wt%, 5wt% to 20wt%, 10wt% to 89wt%, 20wt% to 89wt%, 30wt% to 89wt%, 40wt% to 89wt%, 50wt% to 89wt%, 60wt% to 89wt%, 70wt% to 89wt%, or 80wt% to 89wt%.

[0028] The glass powder of the present invention also contains one or more selected from the group consisting of oxides of group VA elements and oxides of group VB elements. In a preferred embodiment, the formed oxides contained are selected from one or more of the group consisting of P2O5, As2O3, Sb2O3, Sb2O5, Bi2O3, Bi2O5, V2O5, NbO2 and Ta2O5; more preferably, the formed oxides are selected from one or more of the group consisting of P2O5 and V2O5. In the glass powder of the present invention, the oxides of group VA elements and group VB elements used play a role in light transmittance, light resistance and chemical stability. In the embodiment where P2O5 is preferably used, P2O5 can enhance the hardness and heat resistance of the battery electrode, and can also improve the transparency and optical properties of the battery electrode. In the embodiment where As2O3 is preferably used, As2O3 can increase the compressive strength and heat resistance of the battery electrode, and can also improve the chemical stability of the battery electrode. In the embodiment where Sb2O3 or Sb2O5 is preferably used, Sb2O3 or Sb2O5 can enhance the adhesion between the metal grid line and the silicon wafer, thereby improving the reliability of welding, and help improve the photoelectric conversion efficiency of the solar cell in the laser enhanced contact optimization (LECO) technology. In the embodiment where Bi2O3 or Bi2O5 is preferably used, Bi2O3 or Bi2O5 can improve the corrosion resistance of the solar cell and improve the wettability between the metal and the silicon wafer, thereby enhancing the adhesion and current of the grid line, thereby improving the photoelectric conversion efficiency of the solar cell. In the embodiment where V2O5 is preferably used, V2O5 can improve the optical properties and transparency of the battery electrode, and can also increase the heat resistance and chemical stability of the battery electrode. In the embodiment where NbO2 or Ta2O5 is preferably used, NbO2 or Ta2O5 can increase the compressive strength and hardness of the battery electrode, and can also improve the wear resistance and chemical stability of the battery electrode.

[0029] In other embodiments, the shaped oxide of the present invention may include an oxide of a Group IVB element; or preferably, the shaped oxide of the invention may further include an oxide of a Group IVB element when including an oxide of a Group VA element and / or an oxide of a Group VB element. The oxide of a Group IVB element may include one or more of the group consisting of free TiO2, ZrO2 and HfO2; when including an oxide of a Group IVB element, most preferably, the oxide of a Group IVB element is TiO2. In the embodiment where TiO2 is preferably used, TiO2 can enhance the hardness and wear resistance of the battery electrode, and can also improve the light resistance and optical properties of the battery electrode. In the embodiment where ZrO2 is preferably used, ZrO2 can improve the compressive strength and heat resistance of the battery electrode, and can also improve the corrosion resistance and optical properties of the battery electrode. In the embodiment where HfO2 is preferably used, HfO2 can increase the compressive strength and hardness of the battery electrode, and can also improve the heat resistance and chemical stability of the battery electrode.

[0030] In different embodiments of the present invention, the amount of the shaped oxide can be in the following range: 1wt% to 40wt%, 5wt% to 35wt%, 10wt% to 30wt%, 15wt% to 25wt%, 1wt% to 35wt%, 1wt% to 30wt%, 1wt% to 25wt%, 1wt% to 20wt%, 1wt% to 15wt%, 1wt% to 10wt%, 5wt% to 40wt%, 10wt% to 40wt%, 15wt% to 40wt%, 20wt% to 40wt%, 25wt% to 40wt%, 30wt% to 40wt%, or 35wt% to 40wt%.

[0031] In some embodiments of the present invention, the glass powder may further contain 1wt% to 50wt% of other oxides. These other oxides may be selected from one or more of Li2O, Na2O, K2O, MgO, CaO, SrO, BaO, SiO2 and ZnO. In a preferred embodiment, the other oxides are selected from one or more of the group consisting of SiO2, ZnO and Li2O. The addition of the above other oxides is used to improve the mechanical properties and corrosion resistance of the prepared electrode.

[0032] In the embodiment preferably containing Li2O, Li2O can improve the chemical stability and thermal stability of the battery electrode and enhance the impact resistance of the battery electrode. In the embodiment preferably containing Na2O, Na2O can reduce the melting point of the battery electrode, promote the melting of glass, and improve the transparency of the battery electrode. In the embodiment preferably containing K2O, K2O can increase the chemical stability and thermal stability of the battery electrode and improve the chemical corrosion resistance of the battery electrode. In the embodiment preferably containing MgO, MgO can improve the chemical stability and thermal stability of the battery electrode and enhance the heat resistance and mechanical strength of the battery electrode. In the embodiment preferably containing CaO, CaO can improve the chemical stability and thermal stability of the battery electrode and increase the hardness and wear resistance of the battery electrode. In the embodiment preferably containing SrO, SrO can improve the optical properties and UV resistance of the battery electrode and improve the optical transparency of the battery electrode. In the embodiment preferably containing BaO, BaO can increase the density and thermal shock resistance of the battery electrode and improve the strength and durability of the battery electrode. In the embodiment preferably including SiO2, SiO2 determines the basic properties of the prepared battery electrode, such as hardness, tensile strength, chemical stability, etc. In the embodiment preferably including ZnO, ZnO can improve the thermal shock resistance and UV resistance of the battery electrode, and improve the weather resistance and corrosion resistance of the battery electrode.

[0033] In different embodiments of the present invention, the amount of other oxides can be in the following range: 1wt% to 50wt%, 5wt% to 45wt%, 10wt% to 30wt%, 15wt% to 25wt%, 1wt% to 40wt%, 1wt% to 30wt%, 1wt% to 20wt%, 1wt% to 10wt%, 1wt% to 5wt%, 5wt% to 50wt%, 10wt% to 50wt%, 15wt% to 50wt%, 20wt% to 50wt%, 25wt% to 50wt%, 30wt% to 50wt%, 35wt% to 50wt%, 40wt% to 50wt%, or 45wt% to 50wt%.

[0034] In a preferred embodiment of the present invention, the glass powder contains 10wt% to 90wt% of PbO, 5wt% to 90wt% of B2O3, 1wt% to 30wt% of P2O5 or V2O5, and 1wt% to 20wt% of TiO2, wherein the total of all components in the glass powder is 100wt%.

[0035] The paste composition of the present invention further comprises conductive powder, organic carrier and the remainder of additives.

[0036] In a further embodiment, the conductive powder is silver powder, copper powder, aluminum powder, nickel powder, carbon black powder, gold powder, platinum powder, titanium powder or any combination thereof, preferably, the conductive powder is silver powder, and the particle size of the silver powder can be nanometer or micrometer level. For example, the silver powder can have a particle size of tens to hundreds of nanometers, or several to tens of microns. Alternatively, the silver powder can be a mixture of two or more silver powders with different particle sizes. The silver powder can have a spherical, thin or amorphous shape. The silver powder preferably has an average particle size (D50) of about 0.1 μm to about 10 μm, more preferably an average particle size (D50) of about 0.5 μm to about 5 μm. The average particle size can be measured using an instrument such as Mastersize 2000 (Malvern Co., Ltd.) after the conductive powder is dispersed in isopropyl alcohol (IPA) at 25 ° C by ultrasonic waves for 3 minutes. Within this average particle size range, the composition can provide low contact resistance and low line resistance.

[0037] The organic carrier used in the present invention can be any typical organic carrier for solar cell electrode composition, and in a preferred embodiment, the organic carrier can be selected from one or more of the group consisting of organic solvent, adhesive, plasticizer and surfactant. The adhesive resin can be selected from acrylate resin or cellulose resin. Ethyl cellulose is usually used as the adhesive resin. In addition, the adhesive resin can be selected from ethyl hydroxyethyl cellulose, nitrocellulose, ethyl cellulose and phenolic resin blends, alkyd resins, phenol, acrylates, xylene, polybutene, polyester, urea, melamine, vinyl acetate resin, wood rosin, alcohol polymethacrylate, etc. The solvent can be selected from, for example, hexane, toluene, ethyl cellosolve, cyclohexanone, butyl cellosolve, butyl carbitol (diethylene glycol monobutyl ether), dibutyl carbitol (diethylene glycol dibutyl ether), butyl carbitol acetate (monobutyl ether acetate), propylene glycol monomethyl ether, hexylene glycol, terpineol, methyl ethyl ketone, benzyl alcohol, γ-butyrolactone, ethyl lactate and combinations thereof. By mechanically mixing with the inorganic components in the solar cell electrodes, the organic vehicle imparts the appropriate viscosity and rheological properties required for the conductive paste printing process.

[0038] In a further embodiment, the additive is one or more selected from the group consisting of a dispersant, a thixotropic agent, a plasticizer, a viscosity stabilizer, a defoaming agent, a pigment, a UV stabilizer, an antioxidant, and a coupling agent.

[0039] According to some embodiments of the present invention, the paste composition of the present invention comprises 60wt% to 95wt% of a conductive powder, 1.0wt% to 20wt% of an organic vehicle, 0.1wt% to 5wt% of a glass powder, and the remainder of additives, wherein the sum of all components in the paste composition is 100wt%.

[0040] In a preferred embodiment of the present invention, a paste composition for preparing a solar cell electrode comprises a conductive powder, an organic carrier, a glass powder, and the remainder of additives, and wherein the glass powder comprises: 10 wt % to 90 wt % of PbO; 5 wt % to 90 wt % of B2O3; 1 wt % to 40 wt % of ZnO; and 1 wt % to 40 wt % of a forming oxide, wherein the forming oxide is selected from one or more of the group consisting of oxides of group VA elements, oxides of group IVB elements, and oxides of group VB elements, and the sum of all components in the glass powder is 100 wt %.

[0041] In a further preferred embodiment of the present invention, a paste composition for preparing solar cell electrodes comprises a conductive powder, an organic carrier, a glass powder, and the remainder of additives, and wherein the glass powder comprises: 10wt% to 90wt% of PbO; 5wt% to 90wt% of B2O3; 1wt% to 40wt% of ZnO; 1wt% to 30wt% of SiO2; and 1wt% to 40wt% of a forming oxide, wherein the forming oxide is selected from one or more of the group consisting of oxides of group VA elements, oxides of group IVB elements, and oxides of group VB elements, and the sum of all components in the glass powder is 100wt%.

[0042] In the most preferred embodiment of the present invention, a paste composition for preparing a solar cell electrode comprises a conductive powder, an organic carrier, a glass powder, and the remainder of additives, and wherein the glass powder comprises: 10wt% to 90wt% of PbO; 5wt% to 90wt% of B2O3; 1wt% to 40wt% of ZnO; 1wt% to 30wt% of SiO2; and 1wt% to 20wt% of TiO2, the sum of all components in the glass powder being 100wt%.

[0043] According to another typical embodiment of the present invention, a solar cell electrode is provided, which is prepared from the paste composition described above in the present invention.

[0044] According to another typical embodiment of the present invention, a solar cell is provided. The solar cell includes an electrode, and the electrode is a solar cell electrode according to the above description. The solar cell in the present invention can be a solar cell produced by any technology, such as a solar cell produced by laser enhanced contact optimization technology (LECO), back contact cell technology (BC), traditional screen printing technology, chemical vapor deposition (CVD), physical vapor deposition (PVD), atomic layer deposition (ALD), electrochemical deposition (ECD), nanocrystalline chemical solar cell technology, perovskite solar cell technology, thin film solar cell technology, or concentrated solar energy (CPV) technology. In a preferred embodiment of the present invention, the solar cell of the present invention is a solar cell produced by laser enhanced contact optimization technology or a solar cell produced by back contact cell technology.

[0045] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0046] Preparation of solar cell electrode compositions

[0047] The oxides were mixed according to the composition shown in Table 1, and melted and sintered at 900° C. to 1400° C. to prepare a glass frit having an average particle size (D50) of 2.0 μm.

[0048] As an organic binder, 1.0 wt % of ethyl cellulose was fully dissolved in 9.0 wt % of butyl carbitol at 60° C., and 86 wt % of spherical silver powder with an average particle size of 1.5 μm, 1.5 wt % of the prepared glass powder and 0.5 wt % of a thixotropic agent Thixatrol ST were added to the binder solution, followed by grinding in a three-roll mill to prepare a solar cell electrode composition.

[0049] The solar cell electrode composition prepared as above is deposited on the front surface of the monocrystalline silicon wafer in a predetermined pattern by screen printing, and then dried in an infrared drying furnace. Then, the composition for preparing the back aluminum electrode is printed on the back of the wafer and dried in the same manner. The cell processed by the above steps is fired in a belt firing furnace for 40 seconds.

[0050] Test methods

[0051] Photovoltaic IV testing

[0052] The conversion efficiency (%) of the battery was measured using a solar efficiency tester, and the conversion efficiency of the battery was evaluated by measuring the current-voltage (IV) characteristic curve of the solar cell under different light and temperature conditions. The measurement results are shown in Table 1.

[0053] Acid resistance test

[0054] After the sample is exposed to acetic acid at a predetermined concentration for a certain period of time, the sample is taken out and the conversion efficiency of the cell is evaluated using the photovoltaic IV test described above. The acid resistance test result is obtained by the following calculation formula:

[0055] Acid corrosion resistance (%) = [conversion efficiency of uncorroded solar cells (%) - conversion efficiency of solar cells after acetic acid corrosion (%)] / conversion efficiency of uncorroded solar cells (%)

[0056] The measurement results are shown in Table 1.

[0057] Examples 1 to 34 and Comparative Examples 1 to 10

[0058] Examples 1 to 34 and Comparative Examples 1 to 10 use the glass powder composition shown in Table 1 below to prepare compositions for solar cell electrodes in the same manner, and evaluate the conversion efficiency (%) and the degree of efficiency reduction after acetic acid treatment (%) of the prepared solar cells. It should be noted that the examples and comparative examples in Table 1 are intended to highlight the characteristics of one or more inventive examples, rather than to limit the scope of the present invention, nor to indicate that the comparative examples are outside the scope of the present invention. In addition, the subject of the invention is not limited to the specific details described in the examples and comparative examples.

[0059] Table 1

[0060]

[0061]

[0062] It can be seen from the above examples that Examples 1 to 34 of the present invention all exhibit significantly higher conversion efficiencies ranging from 5.9% to a surprising 17.6%, while Comparative Examples 1 to 10 only exhibit conversion efficiencies ranging from 1.5% to 3.7. In addition, the acid corrosion resistance of Examples 1 to 34 of the present invention is significantly better than the results of Comparative Examples 1 to 10, with Example 33 showing an excellent result of 61.3%, which indicates that after corrosion using acetic acid, the conversion efficiency of the solar cell only decreased by 61.3%. Compared with the corrosion resistance results of the embodiments, the acid resistance test results of Comparative Examples 1 to 10 all show an unacceptable decrease in the conversion efficiency of the solar cell of more than 90%.

[0063] Compared with Comparative Example 1, Examples 1, 3 and 5 of the present invention exhibit significantly higher conversion efficiency and lower acid corrosion resistance due to the inclusion of formed oxides (P2O5, TiO2 and V2O5). Examples 7, 8, 11 and 13, which include two or more formed oxides, exhibit even better conversion efficiency.

[0064] In addition, in the case of further containing other oxides, other oxides can improve the conversion efficiency and corrosion resistance of the prepared electrode. However, other oxides should be within the scope specified in the present invention, otherwise the conversion efficiency and corrosion resistance will be unfavorably degraded. For example, in comparative example 10, an excessive amount of 85wt% SiO2 was added, which only showed a conversion efficiency of 1.8% and a 94.8% decrease in efficiency after acetic acid.

[0065] In the embodiments of the present invention, SiO2 is added in embodiments 13 to 16, 30, 31, 33 and 34. The addition of SiO2 increases the chemical stability of the solar cell, so that the solar cell obtains excellent results in the corrosion resistance test. The conversion efficiency of the solar cell in embodiments 13 to 16, 30, 31, 33 and 34 only decreases by 61.3% to 76.2%. ZnO added in embodiments 17 to 24, 29 to 31 and 34 can improve the thermal shock resistance and UV resistance of the battery electrode, thereby also improving the weather resistance and corrosion resistance of the battery electrode. The conversion efficiency of the solar cell in embodiments 19 to 26, 29 to 31 and 34 only decreases by 63.2% to 78.3%, while increasing the photoelectric conversion efficiency of the solar cell. For example, the photoelectric conversion efficiency of the solar cell in embodiment 21 is as high as 17.3%. Li2O and ZnO are added simultaneously in embodiments 30, 31 and 34, which can synergistically enhance the corrosion resistance of the solar cell and effectively improve the photoelectric conversion efficiency of the solar cell.

[0066] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A paste composition for preparing a solar cell electrode, characterized in that: The paste composition is composed of 60 wt % to 95 wt % of conductive powder, 1.0 wt % to 20 wt % of organic vehicle, 0.1 wt % to 5 wt % of glass powder, and the remainder of additives, wherein the total of all components in the paste composition is 100 wt %. Wherein, the glass powder is composed of the following items: 10 to 90 wt % PbO; 5 to 90 wt% B2O3; 1 wt% to 30 wt% of P2O5 or V2O5; and 1wt% to 20wt% TiO2, The total of all components in the glass powder is 100 wt %.

2. The paste composition according to claim 1, characterized in that The additive is selected from one or more of the group consisting of a dispersant, a thixotropic agent, a plasticizer, a viscosity stabilizer, a defoaming agent, a pigment, a UV stabilizer, an antioxidant and a coupling agent.

3. The paste composition according to claim 1, characterized in that The conductive powder is selected from one or more of the group consisting of silver powder, copper powder, aluminum powder, nickel powder, carbon black powder, gold powder, platinum powder and titanium powder.

4. The paste composition according to claim 1, characterized in that The organic vehicle is one or more selected from the group consisting of an organic solvent, a binder, a plasticizer and a surfactant.

5. A solar cell electrode, characterized in that: Prepared from the paste composition according to any one of claims 1 to 4.

6. A solar cell comprising an electrode, characterized in that: The electrode is the solar cell electrode according to claim 5.

7. The solar cell according to claim 6, characterized in that: The solar cell is a solar cell produced using a laser enhanced contact optimization technology or a solar cell produced using a back contact cell technology.

Citation Information

Patent Citations

  • Rapid crystallization glass powder for positive electrode paste of solar cell

    CN104692668A

  • N-type solar cell silver paste doped with organic gallium and preparation method thereof

    CN112786232A

  • Conductive paste and solar cell prepared from same

    CN115602355A

  • Conductive paste composition, preparation method of solar cell and solar cell

    CN117174357A